The Hospital UKM guide to antimicrobial therapy, 2000 - Cheong, Izham (Hospital Universiti Kebangsaan Malaysia (HUKM), 1999)
These guidelines are part of the HUKM Antibiotic Policy and are intended to improve antibiotic prescribing in the hospital.